Analysis of the Implementation of Marketing Strategies to Increase Sales of Siswakoe Insurance Products (Case Study of PT. Asuransi Umum Bumiputera Muda 1967 Syariah Division, Bandung Unit) - Dei Ralegioctve; Karyono (Journal of Business Improvement, 2024)
This study aims to analyze marketing strategies in student insurance products, business competition has become the company's task to improve marketing strategies. Creative and innovative marketing strategies can provide profit potential for the company. One of the marketing strategies carried out at PT. Asuransi uses an agent system. The use of this research method is in the form of qualitative research, primary data sources are obtained from interviews, and secondary data sources are obtained from student product marketing documents. The type of data used is qualitative data, data collection techniques are carried out through searching documents related to marketing strategies for student insurance products, and interviews. Data analysis techniques are descriptive. Based on research conducted, it shows that marketing strategies in increasing sales of student insurance products include using an agent system by distributing brochures person to person or through coordination by sending brochure proposals. As for Ichsan Nurul Hasan, he explained that the principle in sharia insurance is to prioritize the form of mutual assistance and seek halal benefits by using the tabarru fund system, where the contract has the characteristics of voluntary giving or called a grant contract